The journal «Bulletin of the Police» as a source for studying the history of crime in Russian Empire during the First World War - E. E. Shumilova (Омский научный вестник: Серия "Общество. История. Современность")
The paper analyzes the structure and content of the journal «Bulletin of the Police» on the basis of archival materials as a valuable historical source that allows reconstructing data on the dynamics and nature of crime in the Russian Empire during the First World War. From the standpoint of the theory of historical everyday life, it is argued that the distinctive features of the journal «Bulletin of the Police» are the regularity of coverage of criminal crime on the pages of the publication, a wide geographical coverage and a detailed description of events, as well as the publication of court photographs. At the same time, from a source point of view, this publication has a number of drawbacks, among which there is a onesided positive coverage of the work of the police in the fight against crime, the bureaucratic style of presentation of many published articles, as well as the silencing of many problematic issues in the field of studying crime during the war period and measures to combat it. The paper substantiates the conclusion that for a deep and comprehensive scientific analysis of the dynamics of crime in the Russian Empire during the First World War, this historical source contains extremely important information that allows revealing the state of the criminogenic situation from the perspective of everyday life and the activities of police agencies and displaying its results in the public mind.